2007
DOI: 10.1037/1053-0797.17.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Exploring dream work at end of life.

Abstract: Dream work with the terminally ill is an effective intervention modality. Despite this, it remains an understudied phenomenon. This article will review the literature on the subject in an attempt to make recommendations regarding future research into this methodology. The author explores dream work with patients at end-of-life and contrasts it with dream work with trauma survivors. Complementary and alternative medicine interventions used to support the terminally ill are also surveyed. Hypnotic guided imagery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…The subjective reports from participants add to the findings of previous studies suggesting the therapeutic benefits of dream work with the dying, including addressing presenting concerns (Brink, 1977), coming to terms with death (Goelitz, 2001;Muff, 1996), gaining insight and decreasing distress (DeCicco et al, 2010), breaking through isolation to form a therapeutic bond (Goelitz, 2001), facilitating life review (Magee, 1992), and accelerating the therapeutic process (Goelitz, 2001). participants' core concerns, consistent with Goelitz's (2007) assertion. Interpreting dreams with a focus on meaning in life seemed to allow indirect and relatively "safe" access to 3 The quantitative data were collected to augment qualitative findings regarding this sample and should not be generalized due to the small sample size.…”
Section: Implications For Counseling At the End Of Lifesupporting
confidence: 77%
See 2 more Smart Citations
“…The subjective reports from participants add to the findings of previous studies suggesting the therapeutic benefits of dream work with the dying, including addressing presenting concerns (Brink, 1977), coming to terms with death (Goelitz, 2001;Muff, 1996), gaining insight and decreasing distress (DeCicco et al, 2010), breaking through isolation to form a therapeutic bond (Goelitz, 2001), facilitating life review (Magee, 1992), and accelerating the therapeutic process (Goelitz, 2001). participants' core concerns, consistent with Goelitz's (2007) assertion. Interpreting dreams with a focus on meaning in life seemed to allow indirect and relatively "safe" access to 3 The quantitative data were collected to augment qualitative findings regarding this sample and should not be generalized due to the small sample size.…”
Section: Implications For Counseling At the End Of Lifesupporting
confidence: 77%
“…Goelitz (2001) suggested that working with dreams may lessen isolation by contributing to the development of the therapeutic relationship. The emotional catalyst provided by dream work may accelerate the therapeutic process and build the foundation for discussion of difficult topics, such as the grief and loss associated with dying (Goelitz, 2007). The emotional catalyst provided by dream work may accelerate the therapeutic process and build the foundation for discussion of difficult topics, such as the grief and loss associated with dying (Goelitz, 2007).…”
Section: Dreams At the End Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…3,4,11 It has been theorized that ELDVs may be inherent to the dying process, 5 serving to help individuals prepare psychologically and/or spiritually for impending death, and may be an effective platform for exploring and addressing existential distress and concerns. 12,13 ELDVs are often significant and meaningful to both dying individuals and observers, and should, therefore, be viewed as valuable opportunities for both clinicians and family to connect with dying individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Dream work is usually employed with individuals in the course of therapy. Studies on dream work, which indicate the diversity of clients who have engaged in it, have been conducted with specific populations such as cancer patients (Goelitz, 2001), terminally ill patients (Goelitz, 2007), children (Huermann, Heath, Fischer, & Potkar, 2009), and trauma survivors (Gardner & 0mer, 2009). Dream work is also done with groups (Feinberg, 1981 ;Lamb & Hollis, 1994).…”
mentioning
confidence: 99%